UNHCR and accountability: The non-reviewability of UNHCR decisions - Hoi Trinh (Transformation, Integration and Globalization Economic Research (TIGER), 2005)
This paper analyses the role and the conduct of the Office of the United Nations High Commissioner for Refugees after 50 years on the international arena. UNHCR was established to help political migrants in Europe. Currently the organisation assists more than 20 million people worldwide. However, it is believed that this large institution is unable to deal with complex refugee crises, to protect migrants and to secure human rights. The cause for this is lack of certain mechanisms, especially as far as accountability is concerned.
Keywords: 330; Internationale Organisation; Flüchtlinge